Duality of the post-civil war conjure woman in Dolen Perkins-Valdez’s Balm: A Novel - Mohd Amin, Hasyimah (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article examines the duality of the Black woman conjurer in Dolen Perkins-Valdez’s Balm: A Novel (2015) and shows how the protagonist’s migration from the South to post-Emancipation Chicago reshapes her identity and practice. Drawing on Black feminist literary criticism and the cultural history of Hoodoo, the analysis demonstrates how the novel portrays the conjurer as both a bearer of African-based spiritual tradition and a modern figure navigating dislocation and transformation. While the narrative affirms Hoodoo’s historical adaptability, it distinguishes Madge from both traditional “swampers,” who strictly preserve the old ways, and urban exploiters associated with the snake-oil industry. Madge retains the spiritual core of conjure while modifying its practice to suit new cultural demands, such as addressing the psychological health of post–Civil War victims. Her dual positioning reflects a reconstruction of the conjure woman as a progressive figure who embodies cultural memory, mobility, and autonomy within a changing post-Civil War landscape.